2019
DOI: 10.1007/s00167-019-05536-w
|View full text |Cite
|
Sign up to set email alerts
|

Repair within the first 48 h in the treatment of acute Achilles tendon ruptures achieves the best biomechanical and histological outcomes

Abstract: Purpose To compare the biomechanical and histological properties of Achilles tendons repaired at different time points during the acute injury period. Methods Thirty‐six skeletally mature Sprague–Dawley rats underwent bilateral mid‐substance Achilles tenotomy. The Achilles tendons were repaired either in the first 24 h (group 1), 24–48 h (group 2), 48–72 h (group 3), or > 72 h (mean: 120 ± 5.2 h) (group 4) after tenotomy. Six weeks after repair, nine tendons per group were assessed biomechanically and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…This study did not show a significant relationship between time from injury to repair and heel-rise height at 12 months postsurgery. Recently, an animal study 32 reported improved 6-week tendon mechanics in mice treated within 48 hours after injury. In humans, clinical studies 42,50 have shown conflicting outcomes for those undergoing repair within 48 hours of injury.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not show a significant relationship between time from injury to repair and heel-rise height at 12 months postsurgery. Recently, an animal study 32 reported improved 6-week tendon mechanics in mice treated within 48 hours after injury. In humans, clinical studies 42,50 have shown conflicting outcomes for those undergoing repair within 48 hours of injury.…”
Section: Discussionmentioning
confidence: 99%
“…One cannot say that the implanted biomaterial constituted a barrier for the penetration of light emitted by LED, because the membrane was located on the deepest surface of the tendon, that is, the light did not need to pass through it before reaching the tendon. According to Park et al 35 and Misir et al 36 , reducing the inflammatory process in the early stages of repair in tendinous lesions may result in a better quality repair. On the other hand, the greater amount of fibroblasts can optimize the repair process by synthesizing collagen in the extracellular matrix of the tendinous tissue 37 .…”
Section: ■ Discussionmentioning
confidence: 99%
“… 35 and Misir et al . 36 , reducing the inflammatory process in the early stages of repair in tendinous lesions may result in a better quality repair. On the other hand, the greater amount of fibroblasts can optimize the repair process by synthesizing collagen in the extracellular matrix of the tendinous tissue 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Data are based on references for loaded Andersson et al, 2009;Black et al, 2012;Eliasson et al, 2009;Kaux et al, 2012;Khayyeri et al, 2020;Majewski et al, 2018;Müller et al, 2016;Murrell et al, 1997;Murrell et al, 2008;Schizas et al, 2010), mixed loading (Andersson et al, 2009;Eliasson et al, 2011;Eliasson et al, 2012;Freedman et al, 2017a;Hillin et al, 2019;Huegel et al, 2019), and unloaded (Eliasson et al, 2009Eliasson et al, 2011Eliasson et al, 2012;Freedman et al, 2017a;Hammerman et al, 2014;Huegel et al, 2019;Khayyeri et al, 2020;Schizas et al, 2010) rat Achilles tendons. Andersson et al, 2009;Best et al, 1993;Black et al, 2012;Bolt et al, 2007;Devana et al, 2018;Eliasson et al, 2009;Genc et al, 2018;Kaux et al, 2012;Khayyeri et al, 2020;Komatsu et al, 2016;Korntner et al, 2017;Kurt et al, 1999;Majewski et al, 2008;Majewski et al, 2012;Majewski et al, 2018;Misir et al, 2019;Müller et al, 2016;Müller et al, 2018;<...>…”
Section: Cell Populations and Distributionmentioning
confidence: 99%
“…Andersson et al, 2009;Best et al, 1993;Black et al, 2012;Bolt et al, 2007;Devana et al, 2018;Eliasson et al, 2009;Genc et al, 2018;Kaux et al, 2012;Khayyeri et al, 2020;Komatsu et al, 2016;Korntner et al, 2017;Kurt et al, 1999;Majewski et al, 2008;Majewski et al, 2012;Majewski et al, 2018;Misir et al, 2019;Müller et al, 2016;Müller et al, 2018;Murrell et al, 1997;Murrell et al, 2008;Schizas et al, 2010;Staresinic et al, 2003;Usman et al, 2015;Weng et al, 2020;Wieloch et al, 2004) mixed loading (Andersson et al, 2009;Eliasson et al, 2011;Eliasson et al, 2012;Freedman et al, 2017a;Fryhofer et al, 2016;Hillin et al, 2019;, and unloaded (Andersson et al, 2012;Eliasson et al, 2009;Eliasson et al, 2011;Eliasson et al, 2012;Freedman et al, 2017a;Hammerman et al, 2014;Huegel et al, 2019;Khayyeri et al, 2020;Schizas et al, 2010;) rat Achilles tendons. Best et al, 1993;Devana et al, 2018;…”
Section: Cell Populations and Distributionunclassified